(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
In the present study, immediate release solid dispersion of Repaglinide was formulated by solvent evaporation technique. Repaglinide solid dispersions were prepared using PEG 8000, Pluronic F 127 and Gelucire 44/14 by solvent evaporation method. A 3-factor, 3-level central composite design employed to study the effect of each independent variable on dependent variables. FTIR studies revealed that no drug excipient interaction takes place. From powder X-ray diffraction (p-XRD) and by scanning electron microscopy (SEM) studies it was evident that polymorphic form of Repaglinide has been converted into an amorphous form from crystalline within the solid dispersion formulation. The correlation coefficient showed that the release profile followed Higuchi model anomalous behavior and hence release mechanism was indicative of diffusion. From in vivo studies, the AUC0→24 h and peak plasma concentration (Cmax) was doubled when compared with pure drug. In addition, in vitro dissolution efficiency was well correlated with in vivo pharmacokinetic parameters. The obtained results suggested that developed solid dispersion might be an efficacious approach for enhancing the solubility and bioavailability of Repaglinide.